MANAJEMEN LABA SEBAGAI PEMODERASI PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA KINERJA KEUANGAN - Jayastini, Luh Anggi; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of CSR disclosure on the company's financial performance and earnings management as a moderating the effects of CSR on financial performance. The population used in this research is manufacturing companies listed on the Indonesian Stock Exchange (BEI) in the year 2012-2014 as many as 141 companies. Determination of the sample using purposive sampling technique with a sample of 56 observations. Data collected through non-participant observation method. The analysis technique used for the first hypothesis is using linear regression analysis simple and to the second hypothesis using regression analysis moderation. Based on the analysis found that the disclosure of CSR significant positive effect on financial performance proxied by ROE. This indicates that more extensive disclosure of CSR undertaken by the company will further improve financial performance. Analysis of moderating variables showed that earnings management has no influence of CSR on financial performance.
Keywords: Earnings Management, Corporate Social Responsibility (CSR), Financial Performance